'F TEAM' RAHSIA DALAM RAHSIA : Cerita 'Orang Lama'. - Zahriman Alias (RABBANI INTERGRATED, 2021)
Batman risked his life for that purpose and promised to carry it out. "Shoot me to death if I defect," he said. Kenny handed over Batman's Carbine weapon and let him go. Batman enters the communist camp with Tien Chen, his communist friend who was captured by Kenny a few days before. Kenny couldn't hold back the tears from coming out. Tears of love from a very rude senior police officer towards a former communist who had once been his bitterest enemy.